Legislation improvement concerning execution and serving punishment as depriving of will - Рудник, Тетяна Вікторівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In this article an author makes the research of criminal executive law. Analyses herself its practical realizationconcerning execution and serving punishment as depriving of will and international law standards. Anauthor gives a conclusion about necessity of further criminal executive legislation improvement and movesthe correspondent proposals.